Original articleCellular mechanisms of white matter regeneration in an adult dysmyelinated rat model - Kwiecien, Jacek M. (Folia Neuropathologica, 2013)
Cellular mechanisms of regeneration after the white matter injury are difficult to study because of severe, inflammatory response to massively damaged myelin. Myelin-lacking CNS of the adult Long Evans Shaker (LES) rat supplies a model where neuroregeneration can be studied conveniently. The crush site in the dorsal spinal column in LES rats implanted with the normal rat choroid plexus was studied under the light and electron microscopy at 5 time points 3-56 days post-op. While the crush injury in normal rats resulted in severe inflammation active beyond 8 weeks, the same injury in LES rats resulted in a brief inflammation that resolved before day 7 post-op. In a clear fluid-filled crush cavity, ependymal cells from the implanted choroid plexus encased multiple regenerating axons, apparently guided them across the crush cavity and participated in establishing of a zone of neuroregeneration, morphologically similar to the white matter, at the interface of the crush cavity and the surrounding tissue of the spinal cord. Axons that were not encased by implanted cells failed to cross the crush cavity and persisted as markedly swollen end bulbs filled with organelles. At 8 weeks post-op, a large proportion of axons in the zone of neuroregeneration became myelinated by Schwann cells, likely originating from dorsal nerve roots or by oligodendrocytes that formed thin sheaths with a major dense line and likely originated from the implanted choroid plexus. The LES rat can serve as a convenient model to study mechanisms of neuroregeneration including axonal regeneration in the adult CNS injury.